PENGARUH PRICE DAN LIFESTYLE TERHADAP CELEBRITY ENDORSMENT DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA KONSUMEN AINI BATIK DI KABUPATEN TANGERANG TAHUN 2022 - Nur'aini Nur'aini (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The aims of this study are: 1) To determine the effect of Price on Celebrity Endorsement. 2) To determine the effect of Lifestyle on Celebrity Endorsement. 3) To determine the effect of Price on Purchasing Decisions. 4) To determine the significant effect of Lifestyle partially on purchasing decisions. 5) To determine the significant influence of Celebrity Endorsement partially on purchasing decisions. 6) To determine the significant influence of Celebrity Endorsement mediating Price (Price) on purchasing decisions. 7) To determine the significant influence of Celebrity Endorsement mediating Lifestyle on purchasing decisions. The type of research conducted in this research is descriptive research using survey methods. By using a saturated sampling technique, a sample of 75 consumers was taken from Batik in Tangerang Regency. The analytical method in this study was carried out using the Structural Equation Model (SEM). The model used is multiple regression analysis. The results of this study indicate that: 1) There is no effect of Price on Celebrity Endorsement. 2) There is an influence of Lifestyle on Celebrity Endorsement. 3) There is an influence of Price on Purchasing Decisions. 4) There is no Lifestyle influence on Purchasing Decisions. 5) There is an influence of Lifestyle on Purchasing Decisions. 6) Celebrity Endorsement is unable to mediate Price on Purchase Decision. 7) Celebrity Endorsement is able to mediate Lifestyle on Purchasing Decisions